TREES AS THE ROOSTS OF ROSE RINGED PARAKEET IN CENTRAL PUNJAB PAKISTAN - H. A. Khan; W. Majeed; S. Mustafa; S. Shabbir (Journal of Animal and Plant Sciences, 2023)
Present paper describes the impact of trees as roosts for the rose-ringed parakeet (Psittacula krameri Linn.) in the five districts of Central Punjab, Pakistan. The parakeet has established sufficiently large numbers of communal roosts in some of the predominant trees as the Salmalia malabarica, Cedrella toona, Dalbergia sissoo, Azadirachta indica, Terminalia arjuna and others with the suitable ecological conditions. The old and tall trees have occurred here for more than century, offer depressions or hollows. Of these, several after being refined by the parakeets, serve as nests for breeding. Total of six major habitats viz. cropland, villages, roadside plantations, canal sides, city road avenues and the university campus were sampled to determine the overall trees 8769 ± 1.39, cavities 2474 ± 0.97, cavities per tree 10.44 ± 1.78, parakeet nests 528 ± 0.78 and nest percentage proportions 325 ± 1.85 respectively. Significantly, majority of the roosts were closely associated with the economically important food crops viz. wheat, maize, sunflower, sorghum and variety of fruits, therefore, their regular visits to them were frequent to inflict substantial economic losses. The study concludes that although the emphasis to grow more plantations throughout the agro-ecosystems of Central Punjab would prove beneficial; nonetheless population of the parakeets and of the other vertebrate pests would also increase in the ecologically suitable habitats. Therefore, population of such pests should be also estimated accurately and rationalize the strategies the strategies to inhibit the probable depredations on the crops.
Keywords: Roosts; nests; communal; rose-ringed parakeet